Flow visualization of a dielectric barrier discharge plasma actuator - Andrew Ragai, Henry Rigit; Abdul Qayoom, Jakhrani; Ijen, Dakek; Ahsanullah, Soomro (NED University Journal of Research, 2015)
The optimum operating conditions of dielectric barrier discharge (DBD) plasma actuators were determined using both the quantitative and qualitative methods. The quantitative study was carried out by estimating DBD discharge power using the theoretical and experimental methods. The theoretical analysis was carried out to find a mathematical model, which describe the discharge power of the DBD actuator. The estimated results from the mathematical model were compared with the experimental values obtained from Lissajous figures. The qualitative analysis was used for the plasma flow visualization. The effects of the DBD design parameters were studied through the images captured using a high speed charge-coupled device camera. Simulation work was done in order to obtain an insight of the electric field responsible for the plasma formation using the commercial computer software. The results revealed that the performance of the DBD plasma actuator was influenced by various design parameters, especially by dielectric thickness and controlled by the input voltage characteristics.